Small-sided game activities impact the specific motor skills and skill-related competencies of football players between the ages of 12 and 14 years - Mohammed , Omar; Attia , Ahmed (Journal of Physical Education, 2024)
This research aims to investigate the effects of S.S.G. exercises on motor and skill competencies in individuals aged 12 to 14 years. The playing style fulfills several objectives for coaches to enhance the proficiency of their players, particularly in age-specific categories. Motor abilities immediately influence skill capabilities, thereby conferring a significant advantage to the team. Age groups require emphasis since they constitute the essential foundation for elite teams and the extensive base for national teams. Consequently, they ought to be advanced to more rigorous and meticulously designed training to attain superior performance levels. The experimental approach employed a one-group design, with a sample including 15 players from the Baghdad Karkh Sports Talent Center for football. A collection of instruments was utilized, comprising goals of diverse heights and dimensions, ten regulation soccer balls, cones and markers, training platforms of varying elevations, a POLAR-TEAM intensity measuring device, and a protractor. The statistical software (SPSS) was utilized to compute the mean, median, standard deviation, skewness, and T-test for linked samples. The researchers determined that the motor and skill abilities of the study group improved at varying rates; nevertheless, the effectiveness regarding endurance and rolling speed was limited. The activities executed resulted in a more significant enhancement in skill capabilities relative to motor abilities. The implementation of applied exercises tailored for various age groups in training centers involves the design of diverse exercises, configurations, and environments, as well as the number of participants. Additionally, it focuses on developing more effective playing strategies and underscores the utilization of modern equipment to precisely calibrate training intensity standards, including the system. POLAR-TEAM.